Transformation to Ideas of Investments as Economic Category - TUREKULOVA, Asiya N.; TUREKULOVA, Dametken M.; MUHAMBETOVA, Lyazzat K.; BAYBASHEVA, Gulnar К.; KURMANKULOVA, Nurzhamal Zh. (Journal of Advanced Research in Law and Economics; Vol 7 No 5 (2016): Vol 7, No 5(2016): JARLE Volume VII, Issue 5(19), Fall 2016, 2016)
The paper deals with an evolution of views in the economic community on a nature and a purpose of an investment and investment processes in national economy development, as well as systematization of the conceptual framework and methodology offered by national and foreign authors. The author has identified and presented in the article main attributes of investments, explored a systematic approach to the nature of the investment process and described typical directions in the investment activity at a macro and micro levels.
Keywords: investment; investment market; investment activity; investment process